A simulation for acceptance of two-level converters in wind energy systems - Melício, Rui (2014)
This paper focuses on the use of the computational tool Matlab/Simulink to simulate an energy conversion between a variable frequency into and a constant frequency system using a two-level power converter. The simulation of this converter shows an acceptable behavior, justifying the use of a two-level power converter in wind energy systems.